The sodium-glutamate antagonist riluzole improves outcome after acute spinal cord injury: results from the RISCIS randomised controlled trial analysed using a global statistical analytic techniqueResearch in context - Michael G. Fehlings; Karlo M. Pedro; Mohammed Ali Alvi; Ali Moghaddamjou; James S. Harrop; Ralph Stanford; Jonathon Ball; Bizhan Aarabi; Paul M. Arnold; James D. Guest; Shekar N. Kurpad; James M. Schuster; et al. (EBioMedicine)
Summary: Background: Spinal cord injury (SCI) clinical trials typically rely on a single primary endpoint to assess drug efficacy. This strategy fails to adequately capture the full impact of treatment in heterogenous neurological conditions like SCI. A more patient-centric analysis requires assessment of neurological function, functional capacity, and quality of life, incorporating meaningful patient-reported outcomes. The global statistical test (GST) addresses this challenge using a unified statistical conclusion regarding the superiority of a treatment strategy over another by evaluating multiple trial endpoints simultaneously. Methods: The RISCIS trial (Safety and Efficacy of Riluzole in Acute Spinal Cord Injury Study) data was analysed using a multivariate nonparametric GST, integrating the total American Spinal Injury Association (ASIA) motor score (TOTM), Spinal Cord Independence Measure (SCIM), and SF-36 PCS (Short Form-36 Physical Component Scale) scores. In the RISCIS trial, patients with severe cervical SCI (AIS A, B, and C) were randomised to receive riluzole or placebo within 12 h of injury in a double blinded fashion. We compared six-month outcomes between groups using a modified O'Brien's rank sum test with sample variance adjustment. Higher summed ranks represent better global outcomes. The overall probability of improvement was computed using a summary estimate, the global treatment effect (GTE). Findings: A total of 131 patients (mean age 45.8 years old, 82% males) completed the six-month outcome assessment. Among these, 49.6% were classified as AIS A, 20.6% as AIS B, and 29% as AIS C. Riluzole was administered within 12 h from injury for 14 days in 65 patients, while 66 received a placebo. The unadjusted mean change from baseline to six months showed a favourable response in the riluzole group compared to placebo across TOTM (p = 0.28 by t-test; p = 0.26 by Wilcoxon test), SCIM (p = 0.04 by t-test; p = 0.02 by Wilcoxon test), or SF-36 PCS (p = 0.23 by t-test; p = 0.21 by Wilcoxon test) scores. Using the GST to simultaneously assess these measures, the riluzole group exhibited a higher rank sum compared to placebo [median rank sum = 207 (IQR: 166–246) in riluzole vs 185 (IQR: 146–236) in placebo, p = 0.04]. Subgroup analysis revealed the greatest treatment benefit among patients with AIS A injuries (GTE = 0.16, 95% CI: 0.01–0.31, p = 0.02). At six months, the probability that riluzole treatment resulted in overall better outcomes than placebo across all assessed outcomes was 58%. Interpretation: Riluzole was associated with improved global outcomes in patients with severe traumatic SCI, based on a composite score integrating ASIA total motor scores, SCIM, and SF36 outcomes at six months. Riluzole is a promising therapeutic option in SCI, but further investigation through higher-quality studies incorporating multidimensional assessments is warranted. Funding: No funding was received for the present work. The original clinical trial (NCT01597518) was funded by the AO Foundation, United States Department of Defense (DOD), and the Praxis Spinal Cord Institute.